Impact of Educational Games To Introduction Tourist Destination In Central Java On Elementary School Student - Satria, Budi (Yayasan Kita Menulis, 2022)
Educational games are learning media in the form of games that contain material in them. Includes questions, guessing pictures or etcetera. Educational games can also become alternative learning media in the covid-19 pandemic. This study aims to determine the effect of educational games on the understanding of elementary school students regarding the introduction of tourist objects in Central Java. The method is pre-experimental research through pretest and posttest to determine the effect of two variables but there is no control group. Students of SDN 3 Purbalingga Lor are the subjects of this study, with a frequency of 14 students. Pretest data was obtained, the lowest score was 10 and the highest was 70, with an average grade as 33. If you look at posttest results, the highest score was obtained with a score of 100 and the lowest score was 80, with an average grade of 95. This proves the educational games have an effect on the ease of students in understanding the material, especially to know tourist attractions in Central Java.